Acute Heart Failure : Putting the Puzzle of Pathophysiology and Evidence Together in Daily Practice - Krüger, Wolfgang (Springer International Publishing : Imprint: Springer, 2017)
This new and revised edition of this definitive text on this topic provides extensive comprehensive guidance on the management of acute heart failure, the potentially life-threatening situation where correct, rapid therapy can save lives. It presents the latest research and studies and combines this latest understanding of the pathophysiology with a practical guide to diagnosis and management using a thoroughly evidence-based approach. Always keeping the underlying pathophysiology at the forefront of the discussion, Acute Heart Failure encourages readers to understand the underlying pathogenesis and pathobiology of the acute situation and how to direct management in order to address the abnormal physiology. This revision to a seminal text includes new and substantial insights gained over the last few years and represents a valuable source to any practitioner who treats patients with acute heart failure who wants a comprehensive and deeper understanding of the condition, as well as expanding their capacities for an individualized approach to each patient.
Keywords: Medicine.; Human physiology.; Anesthesiology.; Cardiology.; elektronické knihy; electronic books